Structural insight into the glucokinase-ligands interactions. Molecular docking study. (October 2016) - Ermakova, Elena
Graphical abstract: Highlights: Docking simulation was performed to study interaction of glucokinase with ligands. AutoDock and Vina programs accurately reproduce the experimental ligand poses. Correlation between free energy of binding and bioactivity of activators is discussed. Abstract: Glucokinase (GK) plays a key role in the regulation of hepatic glucose metabolism. Inactivation of GK is associated with diabetes, and an increase of its activity is linked to hypoglycemia. Possibility to regulate the GK activity using small chemical compounds as allosteric activators induces the scientific interest to the study of the activation mechanism and to the development of new allosteric glucokinase activators. Interaction of glucokinase with ligands is the first step of the complicated mechanism of regulation of the GK functioning. In this paper, we study the interaction of GK with native (glucose) and synthetic (allosteric activators) ligands using molecular docking method. Calculations demonstrate the ability of molecular docking programs to accurately reproduce crystallized ligand poses and conformations and to calculate a free energy of binding with satisfactory accuracy. Correlation between the free energy of binding and the bioactivity of activators is discussed. These results provide a new insight into protein–ligand interactions and can be used for the engineering of new activators.